Advanced control of doubly fed induction generator for wind power systems - Xu, Dehong; Blaabjerg, Frede 1963-; Chen, Wenjie; Zhu, Nan (IEEE Press series on power engineering, 2018)
Covers the fundamental concepts and advanced modeling techniques of doubly fed induction generators accompanied by analyses and simulation results Filled with illustrations, problems, models, analyses, case studies, selected simulation and experimental results, Advanced Control of Doubly Fed Induction Generator for Wind Power Systems provides the basic concepts for modeling and controlling of doubly fed induction generator "DFIG" wind power systems and their power converters. Other topics of this book include thermal analysis of DFIG wind power converters under grid faults; implications of the DFIG test bench; advanced control of DFIG under harmonic distorted grid voltage, including multiple-loop and resonant control; modeling of DFIG and GSC under unbalanced grid voltage; the LVRT of DFIG, including the recurring faults ride through of DFIG; and more. In addition, this resource: . Explores the challenges and concerns of doubly fed induction generators "DFIG" under non-ideal grid. Discusses basic concepts of DFIG wind power system and vector control schemes of DFIG. Introduces control strategies under a non-ideal grid. Includes case studies and simulation and experimental results Advanced Control of Doubly Fed Induction Generator for Wind Power Systems is an ideal book for graduate students studying renewable energy and power electronics as well as for research and development engineers working with wind power converters